2011
DOI: 10.1080/09540121.2011.555746
|View full text |Cite
|
Sign up to set email alerts
|

Time to first annual HIV care visit and associated factors for patients in care for HIV infection in 10 US cities

Abstract: Having a delayed first annual HIV care visit was associated with higher viremia, lower CD4 cell count, and lack of health insurance. Interventions to address these factors are likely to ameliorate some of the consequences of HIV. For studies enrolling patients in care for HIV over a finite time period, an enrollment period of four-six months should sufficiently reflect the patient population seen in a one-year period, including those attending care infrequently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…A study done in the southeastern US showed that Latinos were more likely to enter into HIV care later in the course of infection (Dennis, Napravnik, Seña, & Eron, 2011). However, Sullivan et al’s (2011) 10 U.S. city study found no relationship between delayed care and race/ethnicity.…”
Section: A Health Disparities Framework For Hiv Infectionmentioning
confidence: 93%
“…A study done in the southeastern US showed that Latinos were more likely to enter into HIV care later in the course of infection (Dennis, Napravnik, Seña, & Eron, 2011). However, Sullivan et al’s (2011) 10 U.S. city study found no relationship between delayed care and race/ethnicity.…”
Section: A Health Disparities Framework For Hiv Infectionmentioning
confidence: 93%
“…Previous investigations have found missed clinic appointments in HIV care to be associated with several critical impacts, including incomplete or protracted timeto-viral suppression (Crawford et al, 2014;Mugavero, Amico, et al, 2012;Sethi, Celentano, Gange, Moore, & Gallant, 2003), premature mortality (Brennan, Maskew, Sanne, & Fox, 2010;Zhang et al, 2012), and clinical therapy failure (Sullivan et al, 2011). Where the end point was mortality, therapy interruption explained the observation, but because HIV clinic-visit consistency is a structural constituent of engagement in care, other mediators may explain the nonmortality outcomes.…”
Section: Introductionmentioning
confidence: 97%
“…Living within these nonexpanding Southern states is especially problematic for PLWH, as they are more likely to be low income and childless and less likely to be privately insured; therefore, they would benefit from expanded Medicaid eligibility based on the ACA. 31 Numerous studies have demonstrated that inadequate health insurance coverage can worsen patient retention in HIV care, [32][33][34][35] and the expansion of safety net programs, such as Medicaid and the Ryan White HIV/AIDS Program, can improve patient clinical outcomes and participation in HIV care. [36][37][38][39] As a Southern state that has not expanded Medicaid, contains many uninsured residents, and possesses a large HIV disease burden, 30,40,41 North Carolina represents a relevant case study among the South to explore the barriers and facilitators to retaining and reengaging HIV clients in care.…”
Section: Introductionmentioning
confidence: 99%